Pulmonary Mycobacterium kansasii infection: comparison of the clinical features, treatment and outcome with pulmonary tuberculosis. - Evans, S. A. (1996)
BACKGROUND: In the United Kingdom Mycobacterium kansasii is the most common pulmonary non-tuberculous mycobacteria to cause disease in the non-HIV positive population. METHODS: The clinical features, treatment, and outcome of 47 patients (13 women) of mean (SD) age 58 (17) years with culture positive pulmonary M kansasii infection were compared with those of 87 patients (23 women) of mean (SD) age 57 (16) years with culture positive pulmonary M tuberculosis infection by review of their clinical and laboratory records. Each patient with M kansasii infection was matched for age, sex, race and, where possible, year of diagnosis with two patients with M tuberculosis infection. RESULTS: All those with M kansasii infection were of white race. Haemoptysis was more common in patients infected with M kansasii but they were less likely to present as a result of an incidental chest radiograph or symptoms other than those due to mycobacterial infection. Patients with M kansasii were also less likely to have a history of diabetes, but the frequency of previous chest disease and tuberculosis was similar. An alcohol intake of > 14 units/week was less frequent in those with M kansasii, but there were no significant differences in drug history, past and present smoking habit, occupational exposures, social class, or marital status. Patients with M kansasii received a longer total course of antimycobacterial therapy and, in particular, extended treatment with ethambutol and rifampicin was given. There was no significant difference in outcome between pulmonary M kansasii or M tuberculosis infection. CONCLUSIONS: There are group differences between the clinical features of the two infections but, with the possible exception of diabetes and alcohol intake, these features are unlikely to be diagnostically helpful. Treatment of M kansasii infection with ethambutol, isoniazid, and rifampicin in these patients was as effective as standard regimens given to patients infected with M tuberculosis.